The World of Sugar: How the Sweet Stuff Transformed Our Politics, Health, and Environment over 2,000 Years - Just, David (Journal of Economic Literature, 2024)
David Just of Cornell University reviews “The World of Sugar: How the Sweet Stuff Transformed Our Politics, Health, and Environment over 2,000 Years” by Ulbe Bosma. The Econlit abstract of this book begins: “Explores the evolution of sugar from luxury to ubiquity, promoting the view that while the contemporary prevalence of sugar is an indication of progress, it also reveals a darker story of human exploitation, racism, obesity, and environmental destruction.”